Improved estimation of fiber length from 3-dimensional images - Ohser, Joachim (Image analysis and stereology, 2013)
A new method is presented for estimating the specific fiber length from 3D images of macroscopically homogeneous fiber systems. The method is based on a discrete version of the Crofton formula, where local knowledge from 3x3x3-pixel configurations of the image data is exploited. It is shown that the relative error resulting from the discretization of the outer integral of the Crofton formula amonts at most 1.2%. An algorithmic implementation of the method is simple and the runtime as well as the amount of memory space are low. The estimation is significantly improved by considering 3x3x3-pixel configurations instead of 2x2x2, as already studied in literature.
Keywords: Crofton formula; stereologija; obdelava slik; image analysis; integral of mean curvature; vlakna; systematic error; ukrivljenost; Croftonova formula; sistemske napake